Hidrotomografía helicoidal: hallazgos en carcinoma y linfoma gástricos - Ocantos, Jorge; Seehaus, Alberto; Genna, Anahí; Celano, Fernando; García Mónaco, Ricardo (Revista del Hospital Italiano de Buenos Aires, 2006)
Traditionally, it has been difficult to thoroughly assess the digestive tract wall by computed tomography due to its incomplete distension and the use of “positive” contrast medium (white), which prevents a precise evaluation of wall alterations produced by different pathological entities. The use of “negative” contrast (dark), and optimal distension of the gastric wall facilitates the discrimination between the enhanced wall (viewed as white), and the perigastric fat or the gastric fluid, both dark colored. Gastric carcinoma and gastric lymphoma usually have similar tomographic parietal thickening, which is the most frequent sign. A suitable gastric distension may accurately differenciate both entities
Keywords: tomography; water; gastric cancer; gastric lymphoma